Digital Innovation and Global Expansion: An Empirical Study of Indonesian Firms' International Diversification (2015-2023) - Pardede, Mahadi; Dirgantari, Puspo Dewi; Gaffar, Vanessa (Ilomata International Journal of Management, 2025)
This research investigates the ramifications of digital technological innovation on the international diversification strategies employed by Indonesian enterprises between the years 2015 and 2023. By applying the resource-based theory alongside the dynamic capabilities framework, we scrutinize the manner in which digital innovations function as strategic assets that facilitate the international expansion of firms. Employing a panel dataset comprising non-financial corporations listed on the Indonesia Stock Exchange, we examine the mediating influence of digital transformation and information asymmetry, as well as the moderating effects attributed to ownership status and industry classification on this nexus. Our empirical findings indicate that digital technological innovation exerts a favorable impact on international diversification, with digital transformation and diminished information asymmetry serving as mediating factors. Furthermore, the degree of this impact exhibits variability contingent upon the type of ownership and industry, revealing a pronounced effect within state-owned enterprises and traditional sectors as opposed to private and digitized industries. These findings highlight the transformative potential of digital technologies in enhancing access to global markets and illuminate the distinctive challenges and prospects present within the Indonesian context. This study offers significant insights for managerial and policy-making practices, accentuating the critical role of digital innovation in formulating strategies aimed at global expansion. Additionally, it contributes to the existing literature on international business by integrating the dynamics of digital innovation within the paradigm of international diversification, particularly within the framework of an emerging market environment.